Seeking new paths by attempting avant-garde teaching methods through translation and creative writing for classes of English for Academic Purposes (EAP) . The cases of the Schools of Engineering, Departments of Mechanical Engineering, Informatics and Tele - CHRISTIDOU, SOFIA; KAMAROUDIS, STAVROS E. (International Journal of Language, Translation and Intercultural Communication, 2016)
The aim of our paper is to discuss how the courses of English Language of the Department of Applied and Visual Arts of the School of Fine Arts and of the Departments of Mechanical Engineering, Informatics and Telecommunications Engineering of the School of Engineering of the University of Western Macedonia were taught during the academic year 2014-5 and how students reacted towards the teaching approaches that were adopted. For reasons of economy of space we present here only the experiment that was conducted in the School of Fine arts. These teaching methods we attempted to implement based on bibliographic research, both during the teaching sessions and in the final assessment, were a) translation and b) creative writing. On the one hand, we tried to familiarize students with the meaning and appropriate use of the terminology of their own scientific fields in both the English and the Greek language and on the other hand we attempted to stir their imagination and create an interest in writing. Our aim was to encourage them to produce their own texts by using knowledge from their own scientific field, express their thoughts, feel more confident when communicating in the foreign language and improve their language skills.